Reichszentralbehörden, regionale Behörden und wissenschaftliche Hochschulen für die zehn westdeutschen Länder sowie Berlin - Boberach, Heinz (Texte und Materialien zur Zeitgeschichte, 1991)
This inventory furnishes for the first time the proof of the whereabouts of therecords of central authorities and institutions of National Socialist Germany inall state archives. In part 1 the records of West Germany and Berlin regardingto this matter are recorded and described according to a special scheme. Thematerial is structured in administrative and organizing units.